APPLYING THE “WORD CHAIN” GAME TO TEACH DESCRIPTIVE SPEAKING TO THE EIGHT GRADERS IN SMPN 26 SURABAYA (RETAIN, 2015)
Abstrak Selamabeberapatahun, kegiatanspeakingdalampelajaranbahasaInggrisdidominasiolehpara guru.Para muridkekurangankesempatanuntukmelatihketerampilanspeakingmereka.Kondisiinimembuatpenguasaankemampuanspeakingmenjadilebihsulitbagimerekadan guru tidakbisamencapaitujuandaripengajaranspeaking. Salah satutujuanpengajaranspeakingdanmungkinmenjaditujuanakhiradalahmembuatmuridmampuberbicaradalambahasa targetdengan natural (Kayi: 2006). Dalampenelitianini, penelitimenggunakanpermainan “word chain” yang telahdimodifikasi, yang manabiasanyadigunakanhanyauntukmeningkatkanperbendaharaan kata saja, untukmengajarspeaking deskriptif. Penelitianinimenggunakanmetodepenelitiandeskriptifkualitatif, karenapenelitianinibertujuanuntukmendeskripsikandanmenjelaskanfenomenaalami: apa yang sedangterjadi?,Mengapahaltersebutterjadi?, danbagaimanahaltersebutterjadi? (Chariri, 2009:9). Penulisfokuspadapenerapanpermainan “word chain” untukmengajarspeaking descriptive danresponsiswaterhadappenerapantersebut.Padabagiananalisis data, penulismendeskripsikan data yang diperolehdariobservasi, bagaimana guru menerapkantekniktersebut, bagaimanapartisipasisiswa, danbagaimanaresponsiswa. Hasil yang diperolehmenunjukkanbahwapermainan ”word chain” dapatditerapkandalamkelasspeakingketikamaterinyaadalahteksdeskriptif. Penulismenemukanbahwapermainantersebuttidakmembutuhkanpersiapan yang lama, tidakmemerlukaninstrumenatau media, danperaturannyamudahuntukdimengerti.Permainaninimendorongsiswauntukberpartisipasilebihaktifdalamkelas, lebihbanyakberbicaradalambahasa target, danmembuatsiswalebihnyamandalammengikutipelajaran. Kata Kunci: keterampilanspeaking, permainan “word chain”, teksdeskriptif Abstract For many years, speaking activity in English class has been dominated by teachers. The students lack opportunities to practise their speaking skill. This condition makes mastering speaking ability is more difficult to them and teachers could not fulfill the aims of teaching speaking. One of the aims of teaching speaking and may be the final target of it is to enable students to speak the language naturally (Kayi: 2006). In this study, the researcher uses the modified word chain game, which is commonly used to improve students’ vocabulary, to teach descriptive speaking. This study uses descriptive qualitative research method, because it aims to describe and to explain a natural phenomenon: what is happening?, why is it happening?, and how is it happening? (Chariri, 2009:9). The writer focuses on the application of the word chain game to teach descriptive speaking and the students’ responses toward it. In the data analysis, the writer describes the data gained from an observation, how the teacher applied the technique, how the students participated, and how the students’ responses were. The result shows that the word chain game is applicable in speaking class where the material is descriptive text. The writer found that game does not require much preparation, does not need any instrument or media, and its rules are easy to understand. It encourages students to participate actively in the class, to speak the target language more, and makes the students enjoy the lesson. Keywords: speaking skill, “word chain” game, descriptive text